Does financial activity cause economic growth? - Michael Graff; Alexander Karmann (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2001)
To clarify the causal links between financial activity and economic growth, three theoretical models are analyzed and a structural equation path models is estimated. In the modeling part, poverty traps result from large fixed costs or high proportions of real investment to run a financial sector. Human capital allocated to financial activities will improve long-run levels but may reduce growth rates in the short run. Empirically, based on data for 93 countries during the 1980-90 period, it is shown that during the 1980s finance was predominantly a supply-leading determinant of economic growth. Our analysis suggests, however, that this general finding cannot be confirmed for the less developed countries, thereby giving some support to the conclusions derived from the theoretical modeling.
Keywords: O16; O42; E24; 330; financial development; economic growth; financial sector; causality; Finanzsektor; Entwicklung; Finanzintermediär; Neue Wachstumstheorie; Schätzung; Theorie; Welt; Entwicklungsländer